Iron-based sintered alloy valve seats for internal combustion engines
By using Si-Cr-Ni-Fe Mo inter-base metal compound particles as hard particles in the iron-based forged aluminum alloy flap base, and dispersion of hard particles and solid lubricant particles in the matrix, the problem of easy cracks and fall off in severe environments is solved, achieving efficient wear protection and sufficient strength.
Patent Information
- Application Number
- JP2023129438
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2021-07-20
- Filing Date
- 2023-08-08
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2042-07-19
AI Technical Summary
The existing Co-free iron-based forged aluminum alloy hard particles are prone to cracks and fall off in severe use environments, resulting in poor wear protection effect, and the hardness of Ni-based hard particles is low and prone to adhesion.
Si-Cr-Ni-Fe Mo inter-base metal compound particles are used as hard particles, and 10% to 40% hard particles and 0% to 5% solid lubricant particles are dispersed in the matrix to form a two-layer structure or a single-layer structure iron-based forged aluminum alloy flap seat.
The hard particles are not prone to cracks and fall off, and the wear protection effect is improved, so that they can show wear protection performance comparable to or better than traditional Co-based hard particles in severe environments, while ensuring sufficient strength and wear resistance.
Smart Images

Figure 0007660623000017 
Figure 0007660623000001 
Figure 0007660623000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a valve seat for an internal combustion engine, and more particularly to a valve seat made of an iron-based sintered alloy having excellent wear resistance. [Background technology]
[0002] Valve seats are press-fitted into the cylinder head of an internal combustion engine, and play the role of sealing the combustion gas and cooling the valve. Because they are exposed to hitting by the valve, wear due to sliding, heating by combustion gas, corrosion by combustion products, etc., traditionally valve seats have been required to have excellent heat resistance and wear resistance, as well as low aggressiveness to the mating material, the valve, so as not to wear it.
[0003] In response to such demands, for example, Patent Document 1 describes a sintered alloy valve seat for internal combustion engines that has excellent wear resistance. The sintered alloy valve seat described in Patent Document 1 is an iron-based sintered alloy valve seat having hard particles and solid lubricant particles dispersed in a matrix phase, the matrix phase being a fine carbide precipitation phase having a particle size of 10 μm or less and a Vickers hardness of 550 HV or more, the matrix phase having a structure in which hard particles having a Vickers hardness of 650 to 1200 HV are dispersed at an area ratio of 20 to 40% and solid phase lubricant particles are dispersed at an area ratio of 0 to 5%, the diffusion phase is formed at an area ratio of more than 0% and 5% or less, the solid lubricant particles are dispersed at an area ratio of 0 to 5%, and the matrix portion including the matrix phase, the diffusion phase, the hard particles, and the solid lubricant particles has a composition including, by mass%, C: 0.5 to 2.0%, Si: 0.5 to 2.0%, Mn: 5% or less, Cr: 2 to 15%, Mo: 5 to 20%, and Co: 2 to 30%. This is said to improve the wear resistance of the valve seat even in severe wear environments.
[0004] Patent Document 2 describes a valve seat made of an iron-based sintered alloy. The valve seat described in Patent Document 2 has a two-layer structure in which a valve seating side portion and a head seating side portion are sintered together. The valve seating side portion has a porosity of 10 to 25% by volume and a density of 6.1 to 7.1 g / cm.3 and a density after sintering of 100% or more. Hard particles are dispersed in a matrix phase, the hard particles being particles made of one or more elements selected from C, Cr, Mo, Co, Si, Ni, S, and Fe, and are dispersed at an area ratio of 5 to 40%. The composition of the matrix phase and the matrix portion including the hard particles is, in mass%, Ni: 2.0 to 23.0%, Cr: 0.4 to 15.0%, Mo: 3.0 to 15.0%, Cu: 0.0 to 0.05%, and the like. The iron-based sintered alloy material contains one or more selected from the group consisting of 0.2-3.0%, Co: 3.0-15.0%, V: 0.1-0.5%, Mn: 0.1-0.5%, W: 0.2-6.0%, C: 0.8-2.0%, Si: 0.1-1.0%, and S: 0.1-1.0% in a total amount of 10.0-40.0%, with the balance being Fe and unavoidable impurities. Note that Patent Document 2 lists Cr-Mo-Co intermetallic compound particles, Ni-Cr-Mo-Co intermetallic compound particles, Fe-Mo alloy particles, Fe-Ni-Mo-S alloy particles, and Fe-Mo-Si alloy particles as examples of the hard particles.
[0005] In the valve seats described in Patent Documents 1 and 2, it is preferable to include a large amount of Co in the matrix phase and hard particles, as this contributes to improving the high-temperature strength and toughness of the matrix phase and improving the wear resistance. However, in recent years, there is a growing concern that the price of Co will rise and it will become difficult to obtain Co due to political instability in producing countries and increased use of Co in other fields such as lithium-ion batteries. Therefore, there is a demand to limit the use of Co.
[0006] In response to such demands, for example, Patent Document 3 proposes an iron-based sintered alloy valve seat. The iron-based sintered alloy valve seat described in Patent Document 3 is an iron-based sintered alloy valve seat having a composition in which hard particles are dispersed in a matrix phase and the overall composition includes, in mass%, Cr: 5.0-20.0%, Si: 0.4-2.0%, Ni: 2.0-6.0%, Mo: 5.0-25.0%, W: 0.1-5.0%, V: 0.5-5.0%, Nb: 1.0% or less, C: 0.5-1.5%, with the balance being Fe and unavoidable impurities. In the iron-based sintered alloy valve seat described in Patent Document 3, it is preferable to use Fe-Mo-Si alloy particles as hard particles, which include, in mass%, Mo: 40.0-70.0%, Si: 0.4-2.0%, C: 0.1% or less, with the balance being Fe and unavoidable impurities.
[0007] Patent Document 4 also proposes a hard particle dispersion type iron-based sintered alloy. The hard particle dispersion type iron-based sintered alloy described in Patent Document 4 is a hard particle dispersion type iron-based sintered alloy in which 3 to 20% of hard particles are dispersed and sintered based on the entire alloy in a matrix containing, by weight percentage, 0.4 to 2% Si, 2 to 12% Ni, 3 to 12% Mo, 0.5 to 5% Cr, 0.6 to 4% V, 0.1 to 3% Nb, 0.5 to 2% C, and the balance Fe. The hard particles contain 60 to 70% Mo, 0.3 to 1% B, 0.1% or less C, and the balance Fe. When B is added to ferromolybdenum-based hard particles, B improves the wettability of ferromolybdenum, prevents the hard particles from falling off the matrix, improves the adhesion between the matrix and the hard particles, and improves the thermal strength and mechanical strength of the sintered alloy. [Prior art documents] [Patent documents]
[0008] [Patent Document 1] JP 2018-90900 A [Patent Document 2] JP 2004-232088 A [Patent Document 3] JP 2015-178650 A [Patent Document 4] JP 2005-325436 A Summary of the Invention [Problem to be solved by the invention]
[0009] However, in the technology described in Patent Documents 3 and 4, the iron-based hard particles not containing dispersed Co are more likely to crack and chip than conventional Co-based hard particles, and the hard particles fall off from the matrix phase, and the desired wear resistance cannot be ensured, especially in the severe valve seat usage environment of recent years. In addition, when commonly used Ni-based hard particles not containing Co are dispersed, there is a problem that the hardness is low and adhesion is likely to occur. Co contributes to the effect of diffusing into the matrix when contained in the hard particles, and promoting the progress of sintering of the matrix when contained in the matrix, and plays a major role in improving the strength of the valve seat. However, in the technology described in Patent Documents 3 and 4, the absence of Co makes it difficult to diffuse alloy elements from the hard particles into the matrix and promote the sintering of the matrix, and it was considered that this is because sufficient strength as a valve seat cannot be obtained.
[0010] In view of the problems of the conventional technology, the present invention aims to provide an iron-based sintered alloy valve seat for internal combustion engines, which has a sintered composition that does not contain Co, has excellent wear resistance, and has sufficient strength as a valve seat. Note that "excellent wear resistance" here refers to a case where the wear resistance is improved compared to a valve seat made of an iron-based sintered alloy having a conventional Co-containing sintered composition. Note that "sufficient strength as a valve seat" here refers to a strength that does not cause cracks or breaks during press-fitting, and can be determined based on the radial crushing strength obtained in accordance with the provisions of JIS Z 2507. [Means for solving the problem]
[0011] In order to achieve the above object, the present inventors first conducted extensive research into the effects on wear resistance of hard particles having a composition that does not contain Co and a matrix phase having a composition that does not contain Co. As a result, they have newly discovered that even hard particles having a composition that does not contain Co can avoid cracking and chipping of the hard particles, ensure hardness, and prevent a decrease in wear resistance by avoiding adhesion between the hard particles and the matrix, thereby ensuring wear resistance equal to or greater than that of conventional Co-based hard particles.
[0012] As a result of further investigation, it was found that the hard particles are preferably Si-Cr-Ni-Fe Mo-based intermetallic compound particles having a composition, by mass%, of 1.5-3.5% Si, 7.0-9.0% Cr, 35.0-45.0% Mo, 5.0-20.0% Ni, with the remainder being Fe and unavoidable impurities.
[0013] First, the experimental results on which the present invention is based will be described. The iron-based powder for forming the matrix phase, the hard particle powder, the alloy element powder, and the solid lubricant powder were adjusted to the blending amounts shown in Table 1, and mixed to obtain a mixed powder. The iron-based powder for forming the matrix phase used was the iron-based powder No. a and No. b with the composition shown in Table 2. The hard particle powder used was the hard particle powder No. MA and No. MD with the composition shown in Table 3. The hard particle powder No. MA is a commonly used Co-based intermetallic compound particle powder, and the hard particle powder No. MD is a Mo-based intermetallic compound particle powder that does not contain Co. The Vickers hardness HV of each particle powder is also shown in Table 3. The solid lubricant particle powder used was MnS particle powder. The mixed powder was blended with 0.75 parts by mass of zinc stearate as a lubricant for 100 parts by mass of the mixed powder.
[0014] The obtained mixed powder was then filled into a metal mold, and formed into a compact of a desired valve seat shape using a powder molding machine, which was then subjected to a dewaxing process and a sintering treatment at 1100°C to 1200°C for 0.5 hours in a reducing atmosphere to obtain a sintered body. The obtained sintered body was further processed, such as cutting and polishing, to obtain an iron-based sintered alloy valve seat of a desired shape and size (outer diameter: 32.1 mmφ × inner diameter: 26.1 mmφ × thickness: 5.5 mm).
[0015] The obtained valve seat (sintered body) was subjected to a hard particle crack resistance test and an abrasion test. The test methods were as follows. (1) Hard particle crack resistance test The cross section of the obtained valve seat (sintered body) was polished, and an indentation was made using a Vickers hardness tester (test force: 0.98 N) so that it was contained within the hard particles (20 particles each) dispersed in the matrix phase, and the presence or absence of cracks in each particle with the indentation was observed using an optical microscope. If a crack occurred outside the indentation, it was determined that a crack had occurred, and the number of particles with cracks (number of cracks) was investigated. The number of cracks in valve seat No. S1 was set as the standard (=1.0), and the ratio of the number of cracks in the hard particles of the valve seat to the standard (crack occurrence ratio) was calculated. (2) Abrasion test A wear test was carried out on the obtained valve seat using a rig tester shown in FIG. 1 under the test conditions shown below. Test temperature: 200℃ (sheet face), Test time: 8 hours, Cam rotation speed: 3000 rpm, Valve speed: 10 rpm, Impact load (spring load): 780N, Valve material: NCF751 equivalent material, Lift amount: 6mm After the test, the amount of wear of the test piece (valve seat) was measured. From the amount of wear obtained, the wear ratio of the valve seat was calculated with the valve seat No. S1 as the standard (=1.00). (3) Radial Crushing Strength Test The radial crushing strength of the obtained valve seat (only the layer on the functional component side) was determined in accordance with the provisions of JIS Z 2507.
[0016] The results obtained are shown in Table 4.
[0017] [Table 1]
[0018] [Table 2]
[0019] [Table 3]
[0020] [Table 4]
[0021] If the valve seat (No. S4) uses hard particle powder No. MD, which is a Mo-based intermetallic compound particle powder with a composition that does not contain Co, cracks or the like will not occur in the hard particles, and it is possible to obtain a valve seat with wear resistance equal to or greater than that of the valve seat (No. S1) in which Co-based intermetallic compound particles are used as hard particles. In other words, it was discovered that by dispersing Si-Cr-Ni-Fe Mo-based intermetallic compound particles with a composition that does not contain Co as hard particles in the matrix phase, it is possible to prevent a decrease in wear resistance.
[0022] Furthermore, the present inventors have found that in order to further improve the wear resistance, in addition to dispersing the hard particles having the above-mentioned composition, the wear resistance can be improved by increasing the proportion of the fine carbide precipitate phase in the matrix phase.
[0023] The present invention was completed based on these findings and further investigations. [1] A valve seat press-fitted into a cylinder head of an internal combustion engine, the valve seat has a two-layer structure in which a functional member-side layer and a support member-side layer are sintered together, The functional component side layer has a structure in which a matrix phase, 10 to 40% by area of hard particles, and 0 to 5% by area of solid lubricant particles are dispersed in the matrix phase, the hard particles have a Vickers hardness of 700 to 1300 HV, and have a composition, by mass%, of 1.5 to 3.5% Si, 7.0 to 9.0% Cr, 35.0 to 45.0% Mo, 5.0 to 20.0% Ni, with the balance being Fe and unavoidable impurities. the matrix phase, the hard particles, and the solid lubricant particles are each an iron-based sintered alloy material having a matrix composition comprising, by mass%, C: 0.5-2.0%, Si: 0.2-2.0%, Mn: 5% or less, Cr: 0.5-15%, Mo: 3-20%, Ni: 1-10%, V: 0-5%, W: 0-10%, S: 0-2%, Cu: 0-5%, with the balance being Fe and unavoidable impurities; the support member side layer is made of an iron-based sintered alloy material having a structure in which a matrix phase, 0-5% by area of solid lubricant particles and 0-5% by area of hardness improver particles are dispersed in the matrix phase, and the matrix portion containing the matrix phase, the solid lubricant particles and the hardness improver particles contains, by mass%, 0.3-1.3% C, 0-2.0% Ni, 0-2.0% Mo, 0-5.0% Cu, 0-5.0% Cr, 0-5.0% Mn, 0-5.0% S, and the balance being Fe and unavoidable impurities; The density of the valve seat is 6.70 to 7.20 g / cm 3 1. A valve seat made of an iron-based sintered alloy for an internal combustion engine, comprising: [2] A valve seat press-fitted into a cylinder head of an internal combustion engine, the valve seat has a single-layer structure including a functional component-side layer, The functional component side layer has a structure in which a matrix phase, 10 to 40% by area of hard particles, and 0 to 5% by area of solid lubricant particles are dispersed in the matrix phase, the hard particles have a Vickers hardness of 700 to 1300 HV, and have a composition, by mass%, of 1.5 to 3.5% Si, 7.0 to 9.0% Cr, 35.0 to 45.0% Mo, 5.0 to 20.0% Ni, with the balance being Fe and unavoidable impurities. the matrix phase, the hard particles, and the solid lubricant particles are each an iron-based sintered alloy material having a matrix composition comprising, by mass%, C: 0.5-2.0%, Si: 0.2-2.0%, Mn: 5% or less, Cr: 0.5-15%, Mo: 3-20%, Ni: 1-10%, V: 0-5%, W: 0-10%, S: 0-2%, Cu: 0-5%, with the balance being Fe and unavoidable impurities; The density of the valve seat is 6.70 to 7.20 g / cm 3 1. A valve seat made of an iron-based sintered alloy for an internal combustion engine, comprising: [3] The iron-based sintered alloy valve seat for internal combustion engines according to [1] or [2], characterized in that the matrix phase of the functional member side layer has a structure consisting of 10 to 90% fine carbide precipitate phase, 0 to 30% high alloy phase, and the remainder pearlite, with the area ratio being 100% being the matrix phase area excluding the hard particles and the solid lubricant particles. [4] The iron-based sintered alloy valve seat for internal combustion engines according to [1] or [2], characterized in that the matrix phase of the functional component side layer has a structure consisting of 0 to 15% high alloy phase and the remainder fine carbide precipitate phase, with the area ratio of the matrix phase excluding the hard particles and the solid lubricant particles being 100%. [5] The iron-based sintered alloy valve seat for internal combustion engines according to [1] or [2], characterized in that the matrix phase of the functional component side layer has a structure consisting of 0 to 25% high alloy phase and the remainder bainite phase, with the area ratio of the matrix phase excluding the hard particles and the solid lubricant particles being 100%. [6] The iron-based sintered alloy valve seat for internal combustion engines according to [1] or [2], characterized in that the matrix phase of the functional component side layer has a structure consisting of 0 to 30% high alloy phase and the remainder pearlite, with the area ratio of the matrix phase excluding the hard particles and the solid lubricant particles being 100%. [7] The valve seat made of an iron-based sintered alloy for an internal combustion engine according to [3] or [4], characterized in that the fine carbide precipitate phase is a phase in which fine carbides having a grain size of 10 μm or less are precipitated and has a Vickers hardness of 400 to 600 HV. [8] The valve seat made of an iron-based sintered alloy according to any one of [1] to [7], characterized in that the solid lubricant particles are one or two types selected from manganese sulfide (MnS) and molybdenum disulfide (MoS2). [9] The valve seat made of an iron-based sintered alloy according to [1], wherein the hardness improving particles are iron-molybdenum alloy particles. Effect of the Invention
[0024] According to the present invention, even in a severe wear environment, cracking or chipping of the hard particles is reduced, and no adhesion occurs, so that a valve seat having excellent wear resistance can be obtained, which is extremely effective in industry. [Brief description of the drawings]
[0025] [Figure 1] FIG. 1 is an explanatory diagram showing an overview of a rig testing machine. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0026] The valve seat of the present invention is made of an iron-based sintered alloy and has a two-layer structure in which a functional member side layer on which the valve seats and a support member side layer that seats on the cylinder head and supports the functional member side layer are sintered together, or has a single-layer structure consisting of only the functional member side layer.
[0027] The iron-based sintered alloy material constituting the functional member side layer of the valve seat of the present invention has a structure in which hard particles or further solid lubricant particles are dispersed in the matrix phase, and has excellent wear resistance. Note that "excellent wear resistance" here means that the wear resistance is improved to the same level or higher than that of the iron-based sintered alloy material having a conventional Co-containing sintered body composition.
[0028] In the functional component side layer of the valve seat of the present invention, the hard particles dispersed in the matrix phase are Si-Cr-Ni-Fe Mo-based intermetallic compound particles having a Vickers hardness of 700 to 1300 HV.
[0029] If the hardness of the hard particles is less than 700HV, the hard particles themselves will adhere to each other, and the effect of improving wear resistance will be small, while if the hardness exceeds 1300HV, the toughness of the hard particles will decrease and the machinability will decrease. For these reasons, the hardness of the hard particles dispersed in the matrix phase is limited to the range of 700 to 1300HV in Vickers hardness.
[0030] In the present invention, the hard particles dispersed in the matrix phase preferably have the above hardness and an average particle size of 10 to 150 μm. If the average particle size is less than 10 μm, the particles are likely to diffuse during sintering, whereas if it exceeds 150 μm, the bonding strength with the matrix decreases, and the wear resistance decreases. For this reason, it is preferable to limit the average particle size of the hard particles dispersed in the matrix phase to the range of 10 to 150 μm. Here, the "average particle size" refers to the particle size D50 at which the cumulative distribution measured by the laser scattering method is 50%.
[0031] In the present invention, the hard particles having the above hardness are dispersed in the matrix phase at an area ratio of 10 to 40%. If the amount of dispersed hard particles is less than 10%, the desired wear resistance cannot be ensured. On the other hand, if the amount of dispersed hard particles exceeds 40%, the binding force with the matrix phase decreases, and the wear resistance decreases. For this reason, the amount of dispersed hard particles in the matrix phase is limited to a range of 10 to 40% in area ratio to the entire matrix phase.
[0032] In the present invention, the Si-Cr-Ni-Fe Mo-based intermetallic compound particles dispersed in the matrix phase are Mo-based intermetallic compound particles having a composition (hard particle composition) containing, by mass%, 1.5-3.5% Si, 7.0-9.0% Cr, 35.0-45.0% Mo, 5.0-20.0% Ni, with the remainder being Fe and unavoidable impurities.
[0033] By using hard particles having the above-mentioned hard particle composition, a valve seat including hard particles having a structure in which intermetallic compounds are precipitated after sintering can be obtained. In addition, in order to obtain hard particles having a Vickers hardness of 700HV or more, suppressing the occurrence of cracks, chipping, etc., and precipitating intermetallic compounds having high hard particle crack resistance, it is important to maintain the Mo content as high as 35.0 to 45.0%. In addition, in order to obtain hard particles having further toughness and maintaining a desired hardness, it is important to keep the Ni content in the range of 5.0 to 20.0%.
[0034] In addition, in the functional component side layer of the valve seat of the present invention, solid lubricant particles may be further dispersed in the matrix phase. By dispersing the solid lubricant particles in the matrix phase, machinability and lubricity are improved. However, if the solid lubricant particles are dispersed at an area ratio exceeding 5%, the mechanical properties are significantly deteriorated. For this reason, the area ratio of the solid lubricant particles is limited to a range of 0 to 5%. The solid lubricant particles are preferably one or two types selected from manganese sulfide MnS and molybdenum disulfide MoS2.
[0035] The matrix phase of the functional member-side layer of the valve seat of the present invention has a structure consisting of 10-90% fine carbide precipitate phase, 0-30% high alloy phase and the remainder pearlite, or 0-15% high alloy phase and the remainder fine carbide precipitate phase, or 0-25% high alloy phase and the remainder bainite phase, in terms of the area ratio of the matrix phase excluding hard particles and solid lubricant particles as 100%. The fine carbide precipitate phase is a hard phase in which fine carbides having a particle size of 10 μm or less are precipitated and has a Vickers hardness of 400-600 HV. The presence of such a hard fine carbide precipitate phase strengthens the matrix and further improves the wear resistance. In the functional member-side layer of the valve seat of the present invention, the matrix phase excluding hard particles and solid lubricant particles may have a structure consisting of 0-30% high alloy phase and the remainder pearlite. Even with such a structure of the matrix phase, a sintered body having a composition that does not contain Co has improved wear resistance compared to a sintered body having a composition that contains Co at the same hardness level.
[0036] The high alloy phase is a region where the alloying elements diffuse from the hard particles during sintering and the alloy content is high, and has the effect of preventing the hard particles from falling off. In the functional component side layer, the high alloy phase can be tolerated at an area ratio of up to 30% when the area of the matrix phase excluding the hard particles and solid lubricant particles is taken as 100%.
[0037] In this manner, the functional component side layer of the valve seat of the present invention has a structure in which a predetermined amount of hard particles having the above-mentioned composition, structure and hardness, and solid lubricant particles having the above-mentioned composition are dispersed in the matrix phase of the above-mentioned structure.
[0038] In the functional component side layer of the valve seat of the present invention, the matrix including the matrix phase, hard particles and solid lubricant particles has a matrix composition containing, by mass%, C: 0.5-2.0%, Si: 0.2-2.0%, Mn: 5% or less, Cr: 0.5-15%, Mo: 3-20%, Ni: 1-10%, V: 0-5%, W: 0-10%, S: 0-2%, Cu: 0-5%, with the balance being Fe and unavoidable impurities.
[0039] Next, the reasons for limiting the composition of the matrix of the functional member side layer will be explained. Note that hereinafter, mass % in the composition will be simply indicated as %.
[0040] C: 0.5-2.0% C is an element necessary for adjusting the matrix phase to a predetermined hardness and structure, or for forming carbides, and is contained at 0.5% or more. On the other hand, if it is contained in excess of 2.0%, the melting point drops, and the sintering process becomes liquid phase sintering. When liquid phase sintering occurs, the amount of precipitated carbides becomes too large, the number of voids increases, and the elongation properties and dimensional accuracy decrease. For this reason, C is limited to the range of 0.5 to 2.0%. The C content is preferably 0.50 to 2.00%, and more preferably 1.00 to 1.50%.
[0041] Silicon: 0.2 to 2.0% Silicon is an element contained mainly in hard particles and constitutes an intermetallic compound. It increases the hardness of the hard particles, increases the matrix strength, and improves wear resistance. For this reason, it is preferable to contain 0.2% or more. On the other hand, if it is contained in excess of 2.0%, aggressiveness against the mating member increases. For these reasons, the silicon content is limited to the range of 0.2 to 2.0%. The range is preferably 0.20 to 2.00%. The range is more preferably 0.20 to 1.40%.
[0042] Mn: 5% or less Mn is an element that increases the hardness of the matrix phase. Mn is also contained in the matrix due to solid lubricant particles and contributes to improving machinability, and is preferably contained at 0.05% or more. On the other hand, if it is contained at more than 5%, the hardness, toughness, and ductility of the matrix phase decrease. For this reason, Mn is limited to a range of 5% or less. The content is preferably 5.00% or less, and more preferably 0.20 to 3.00%.
[0043] Cr: 0.5~15% Cr dissolves in the matrix phase and forms carbides to increase the hardness of the matrix phase, and as a constituent element of intermetallic compounds, Cr contributes to increasing the hardness of hard particles, so it is preferable to include 0.5% or more in the matrix. On the other hand, if it exceeds 15%, Cr carbides will precipitate excessively in the matrix phase, making it difficult to make the carbides in the matrix phase fine. For this reason, Cr is limited to the range of 0.5 to 15%. The Cr content is preferably 1.00 to 15.00%, and more preferably 0.70 to 6.00%.
[0044] Mo: 3-20% Mo dissolves in the matrix phase and precipitates as carbides to increase the hardness of the matrix phase. Furthermore, Mo is an element that contributes to increasing the hardness of hard particles as a constituent element of intermetallic compounds, and is preferably contained in the matrix at 3% or more. On the other hand, if it exceeds 20%, it is difficult to increase the density during powder molding, and moldability decreases. For this reason, Mo is limited to the range of 3 to 20%. The range is preferably 4.00 to 20.00%, and more preferably 4.00 to 19.00%.
[0045] Ni: 1-10% Ni is an element that contributes to improving the strength and toughness of the matrix phase, and also contributes to increasing the hardness of hard particles as a constituent element of intermetallic compounds, and is contained in an amount of 1% or more. On the other hand, if the content exceeds 10%, it becomes difficult to increase the density during powder molding, and moldability decreases. For this reason, Ni is limited to the range of 1 to 10%. The Ni content is preferably 1.00 to 10.00%, and more preferably 2.00 to 9.00%.
[0046] The above-mentioned components are the basic components, but the following optional elements may also be contained: V: 0-5%, W: 0-10%, S: 0-2%, and Cu: 0-5%.
[0047] V: 0~5% V is an element that precipitates as fine carbides, increases the hardness of the matrix phase, and improves wear resistance, and can be contained as necessary. When contained, it is preferable that the content is 0.5% or more. On the other hand, a content exceeding 5% reduces formability. For this reason, it is preferable that the V content is limited to the range of 0 to 5%. More preferably, it is 5.00% or less, and further preferably, it is 2.00% or less.
[0048] W: 0~10% W is an element that precipitates as fine carbides, increases the hardness of the matrix phase, and improves wear resistance, and can be contained as necessary. When W is contained, it is preferable that it is contained in an amount of 0.5% or more. On the other hand, a content of more than 10% reduces formability. For this reason, it is preferable that W is limited to the range of 0 to 10%. In addition, it is more preferably 10.00% or less, and further preferably 5.00% or less.
[0049] S: 0-2% S is an element contained in the solid lubricant particles and in the matrix, which contributes to improving machinability, and can be contained as necessary. If the S content exceeds 2%, it leads to a decrease in toughness and ductility. For this reason, it is preferable to limit S to the range of 0 to 2%, and more preferably to 2.00% or less.
[0050] Cu: 0-5% Cu is an element that contributes to improving the strength and toughness of the matrix phase, and can be contained as necessary. If Cu is contained in an amount exceeding 5%, it leads to a decrease in adhesion resistance. Therefore, it is preferable to limit Cu to the range of 0 to 5%, and more preferably to 5.00% or less.
[0051] The balance other than the above components consists of Fe and unavoidable impurities. Note that as for the unavoidable impurities, P: 0.1% or less is permissible.
[0052] The iron-based sintered alloy material constituting the support member side layer of the valve seat of the present invention has a structure in which a base phase and solid lubricant particles and hardness improving particles are dispersed in the base phase at an area ratio of 0 to 5% and 0 to 5%, respectively. The base phase of the support member side layer of the valve seat of the present invention is preferably a structure consisting of 100% pearlite or 100% bainite phase in terms of area ratio when the base phase area excluding the solid lubricant particles and the hardness improving particles is taken as 100%. The base phase can be allowed to contain a high alloy phase up to an area ratio of 5% when the base phase area excluding the solid lubricant particles is taken as 100%. The hardness improving particles are preferably iron-molybdenum alloy (also called Fe-Mo alloy or ferro-molybdenum alloy) particles. The Fe-Mo alloy particles are preferably particles containing, for example, 60 mass% Mo, with the remainder consisting of Fe and unavoidable impurities.
[0053] In the support member side layer of the valve seat of the present invention, the matrix portion including the matrix phase, solid lubricant particles and hardness improving particles contains, by mass%, 0.3-1.3% C, 0-2.0% Ni, 0-2.0% Mo, 0-5.0% Cu, 0-5.0% Cr, 0-5.0% Mn, 0-5.0% S, and the remainder being Fe and unavoidable impurities. The reasons for limiting the composition of the matrix portion of the support member side layer are as follows.
[0054] C: 0.3 to 1.3% C is an element necessary for adjusting the matrix phase of the support member side layer to a predetermined hardness and structure, or for forming carbides, and is contained at 0.3% or more. On the other hand, if it is contained at more than 1.3%, the melting point decreases and the sintering process becomes liquid phase sintering. When it becomes liquid phase sintering, the amount of precipitated carbides becomes too large, and the elongation characteristics and dimensional accuracy decrease. For this reason, C is limited to the range of 0.3 to 1.3%. The C content is preferably 0.30 to 1.30%, and more preferably 0.80 to 1.20%.
[0055] Ni:0~2.0%, Mo:0~2.0%, Cu:0~5.0%, Cr:0~5.0% Ni, Mo, Cu, and Cr are all elements that increase the hardness of the matrix phase, and can be contained as necessary. In order to obtain such effects, it is desirable to contain Ni: 0.1% or more, Mo: 0.1% or more, Cu: 0.1% or more, and Cr: 0.1% or more. On the other hand, if the contents exceed Ni: 2.0%, Mo: 2.0%, Cu: 5.0%, and Cr: 5.0%, respectively, the formability of the matrix phase decreases. For this reason, it is preferable to limit the contents to the ranges of Ni: 0-2.0%, Mo: 0-2.0%, Cu: 0-5.0%, and Cr: 0-5.0%. More preferably, Ni: 2.00% or less, Mo: 2.00% or less, Cu: 5.00% or less, and Cr: 5.00% or less.
[0056] Mn: 0-5.0%, S: 0-2.0% Both Mn and S are elements contained in the matrix due to the inclusion of solid lubricant particles, and contribute to improving machinability, and can be contained as necessary. Mn also contributes to increasing the hardness of the matrix phase. If S exceeds 2.0% and Mn exceeds 5.0%, the ductility decreases significantly. For this reason, it is preferable to limit S to 0-2.0% and Mn to 0-5.0%. More preferably, S is 2.00% or less and Mn is 5.00% or less.
[0057] The balance of the support member side layer other than the above-mentioned components is Fe and unavoidable impurities, of which P: 0.1% or less is permissible.
[0058] Next, a preferred method for producing the valve seat of the present invention will be described. First, the raw powder for the functional member side layer and the raw powder for the support member side layer are blended and mixed to obtain the above-mentioned matrix phase composition and structure, and the matrix portion composition and structure, respectively, to obtain the mixed powder for the functional member side layer and the mixed powder for the support member side layer. The raw powder for the functional member side layer is blended with an iron-based powder for forming the matrix phase, an alloy element powder, a hard particle powder, and a solid lubricant particle powder, so as to obtain the above-mentioned predetermined composition and structure. The raw powder for the support member side layer is blended with an iron-based powder for forming the matrix phase, and graphite powder, or further alloy element powder, solid lubricant particle powder, and hardness improving particle powder, so as to obtain the above-mentioned predetermined composition and structure. It is preferable that the hard particle powder blended into the mixed powder as the raw powder is obtained by melting a molten metal having the above-mentioned hard particle composition by a conventional melting method, and forming a powder (hard particle powder) by a conventional atomizing method.
[0059] The iron-based powder to be mixed in the mixed powder is preferably any one of atomized pure iron powder, reduced iron powder, and alloy steel powder, or a mixture thereof. The alloy steel powder is preferably a powder having a high-speed tool steel composition defined in JIS G 4403 so that a fine carbide precipitate phase having the above-mentioned hardness can be formed as the base phase. The high-speed tool steel is preferably a Mo-based steel such as SKH51. There is no problem in using an alloy steel having the above-mentioned hardness and a composition capable of forming a fine carbide precipitate phase or a bainite phase other than the high-speed tool steel composition. It goes without saying that the mixed powder is mixed with pure iron powder, or with pure iron powder and alloy steel powder having the above-mentioned composition, or with alloy steel powder having the above-mentioned composition, with graphite powder and further with alloy element powder so as to form the above-mentioned base phase composition. The mixed powder may be mixed with a lubricant such as zinc stearate.
[0060] The resulting mixed powder is then filled into a die and molded with a powder molding machine or the like to produce a valve sheet-shaped green compact of predetermined dimensions. In the case of a two-layer structure, the raw material powder for the support member side layer and the raw material powder for the functional component side layer are successively filled into the die to form two layers. On the other hand, in the case of a single-layer structure, the raw material powder for the functional component side layer is filled into the die.
[0061] The resulting green compact is then subjected to a sintering process to produce a sintered body. The sintering treatment is preferably performed in a reducing atmosphere such as ammonia decomposition gas or vacuum at a heating temperature in the range of 1100 to 1200°C for 0.5 hours or more. It goes without saying that the powder molding-sintering treatment may be performed once (1P1S) or may be repeated several times (2P2S, etc.). The obtained sintered body is processed by cutting, grinding, etc. to form a valve seat of desired dimensions and shape.
[0062] The present invention will be further described below with reference to examples. EXAMPLES
[0063] Example 1 First, a powder mixture for the functional member side layer and a powder mixture for the support member side layer were prepared. The mixed powder for the functional member side layer was prepared by adjusting the blending amounts of iron-based powder for forming the matrix phase, graphite powder, alloying element powder, hard particle powder, and solid lubricant particle powder (MnS powder) shown in Table 7, and mixing them to obtain a mixed powder. The iron-based powder used was pure iron powder (atomized pure iron powder, reduced iron powder), high-speed steel powder, and alloy steel powder with the compositions shown in Table 5. The hard particle powder used was hard particle powder with the composition shown in Table 6. Hard particle powder No. A is a commonly used Co-based intermetallic compound particle powder, and is a conventional example. Table 6 also lists the Vickers hardness HV and average particle diameter D50 before sintering for each hard particle.
[0064] The mixed powder for the support member side layer was prepared by mixing an iron-based powder for forming the matrix phase, a graphite powder, an alloying element powder, a hardness improving particle powder, and a solid lubricant particle powder (MnS powder) in the amounts shown in Table 8. The iron-based powder used was a pure iron powder (atomized pure iron powder, reduced iron powder) having the composition shown in Table 5. The hardness improving particle powder used was an iron-molybdenum alloy particle powder having a composition containing 60 mass % Mo, with the remainder being Fe and unavoidable impurities.
[0065] The mixed powder contained 0.75 parts by mass of zinc stearate as a lubricant relative to 100 parts by mass of the mixed powder.
[0066] Next, the obtained mixed powder for the functional member side layer and the mixed powder for the support member side layer were sequentially filled into a die so as to form two layers, and a powder compact having a predetermined valve seat shape was molded using a powder molding machine. Note that the valve seat No. 17A was a single layer consisting of only the functional member side layer.
[0067] Next, the obtained green compact was further subjected to a degreasing process for removing the lubricant and a sintering process at 1100° C. to 1200° C. for 0.5 hr in an ammonia decomposition gas to obtain a sintered compact. In some cases, the powder molding and sintering processes were carried out twice (2P2S).
[0068] The obtained sintered body was further subjected to machining such as cutting and polishing to obtain an iron-based sintered alloy valve seat having a predetermined shape and dimensions (outer diameter: 32.1 mmφ×inner diameter: 26.1 mmφ×thickness: 5.5 mm).
[0069] The obtained valve seat (sintered body) was analyzed for the composition of the matrix at each part of the sintered body, and further subjected to structure observation, hardness measurement, density measurement, hard particle crack resistance test, wear test, and radial crushing strength test. The test methods were as follows. (1) Tissue Observation The cross section perpendicular to the axial direction of the obtained valve seat was polished and etched (etching liquid: nital liquid, marble liquid) to reveal the structure, and the structure of the base phase was identified using an optical microscope (magnification: 200 times). In addition, the grain size of the carbide precipitated in the base phase was measured using a scanning electron microscope (magnification: 2000 times), and it was confirmed that the grain size (long side length) of the carbide was 10 μm or less at maximum, and that the phase in which the carbide precipitated was a fine carbide precipitate phase. When the grain size (long side length) of the carbide was more than 10 μm at maximum, it was determined to be a carbide precipitate phase. (2) Hardness test The cross section of the obtained valve seat was polished and etched (etching liquid: nital liquid, marble liquid) to reveal the structure, and the hardness of the matrix was measured using a Vickers hardness tester (test force: 0.98 N). When the matrix was two-phase, the hardness was measured separately. (3) Density test The density of the obtained valve seat was measured by the Archimedes method. (4) Hard particle crack resistance test The cross section of the obtained valve seat was polished, and an indentation was made on the hard particles (20 each) dispersed in the matrix phase using a Vickers hardness tester (test force: 0.98 N). The presence or absence of cracks in each particle with the indentation was observed, and the number of cracks was investigated. Note that it was determined that cracks had occurred if the cracks had progressed outside the indentation when observed at a magnification of 500 times. Then, the number of cracks in the valve seat No. 1A, which is a conventional example, was set as the standard (=1.0), and the ratio of the number of cracks in the hard particles of the valve seat to the standard (crack occurrence ratio) was calculated. From the obtained results, a crack occurrence ratio of less than 1.0 was evaluated as ◯ (crack resistance), and a crack occurrence ratio of 1.0 or more was evaluated as × (no crack resistance). (5) Abrasion test A wear test was carried out on the obtained valve seat using a rig tester shown in FIG. 1 under the test conditions shown below. Test temperature: 200℃ (sheet face), Test time: 8 hours, Cam rotation speed: 3000 rpm, Valve speed: 10 rpm, Impact load (spring load): 780N, Valve material: NCF751 equivalent material, Lift amount: 6mm After the test, the amount of wear of the test piece (valve seat) was measured. From the amount of wear obtained, the wear ratio of the valve seat was calculated with the conventional valve seat No. 1A as the standard (=1.00). (6) Radial crushing strength The valve seat obtained (only the functional component side layer) was subjected to radial crushing strength (kg / mm 2The radial crushing strength was 40 kg / mm 2 If the material meets the above criteria, it has been confirmed that the material has sufficient strength to function as a valve seat without cracking or chipping when the valve seat is pressed into place.
[0070] The valve seat No. 1A (conventional example) used as the standard in the hard particle cracking resistance test and wear test is an iron-based sintered alloy material with a structure in which hard particles and solid lubricant particles are dispersed in the matrix phase and a Co-containing composition in the functional component side layer, and is a material used for a wide range of exhaust side valve seats from general gasoline engines to high-performance gasoline engines. The degree of influence of items that affect the wear resistance of valve seats (for example, thermal load, design values of the valve mechanism, etc.) differs between the exhaust side and the intake side, and the exhaust side is generally used in a harsher environment, so the wear resistance of the valve seat requires performance that is higher than that of the intake side.
[0071] The results obtained are shown in Tables 9 and 10.
[0072] [Table 5]
[0073] [Table 6]
[0074] [Table 7]
[0075] [Table 8]
[0076] [Table 9]
[0077] [Table 10]
[0078] None of the examples of the present invention (reference examples) contain Co, and they have excellent wear resistance equal to or greater than that of the conventional example (valve seat No. 1A), and also have sufficient radial crushing strength as a valve seat. On the other hand, the comparative examples outside the scope of the present invention have a higher wear ratio than the conventional example (valve seat No. 1A).
[0079] Example 2 First, a powder mixture for the functional member side layer and a powder mixture for the support member side layer were prepared. The mixed powder for the functional member side layer was prepared by adjusting the blending amounts of iron-based powder for forming the matrix phase, graphite powder, alloying element powder, hard particle powder, and solid lubricant particle powder (MnS powder) shown in Table 13 and mixing them to obtain a mixed powder. The iron-based powder used was a pure iron powder (atomized pure iron powder, reduced iron powder) and an alloy iron powder (prealloy powder) having the composition shown in Table 11. The hard particle powder used was a hard particle powder having the composition shown in Table 12. Hard particle powder No. A was a commonly used Co-based intermetallic compound particle powder, and mixed powder D1 containing hard particle powder No. A was a conventional example. Table 12 also lists the Vickers hardness HV and average particle diameter D50 of each hard particle before sintering.
[0080] The mixed powder for the support member side layer was prepared by adjusting and mixing the iron-based powder for forming the matrix phase, graphite powder, alloy element powder, and hardness improving particle powder in the amounts shown in Table 14. The iron-based powder used was pure iron powder (atomized pure iron powder) No. a with the composition shown in Table 11. The hardness improving particle powder used was iron-molybdenum alloy particle powder Fe-Mo with a composition containing 60 mass% Mo, the remainder being Fe and unavoidable impurities. No solid lubricant particle powder (MnS powder) was added.
[0081] The mixed powder contained 0.75 parts by mass of zinc stearate as a lubricant relative to 100 parts by mass of the mixed powder.
[0082] Next, the obtained functional member side layer mixed powder and the support member side layer mixed powder were sequentially filled into a die so as to form two layers, and a green compact having a predetermined valve seat shape was molded using a powder molding machine. Next, the obtained green compact was further subjected to a degreasing process to remove the lubricant, and a sintering process (1P1S) in ammonia decomposition gas at 1100-1200℃×0.5hr to obtain a sintered compact.
[0083] The obtained sintered body was further subjected to machining such as cutting and polishing to obtain an iron-based sintered alloy valve seat having a predetermined shape and dimensions (outer diameter: 32.1 mmφ×inner diameter: 26.1 mmφ×thickness: 5.5 mm).
[0084] The obtained valve seat (sintered body) was analyzed for the composition of the matrix at each portion of the sintered body, and further subjected to structure observation, hardness measurement, density measurement, hard particle crack resistance test, wear test, and radial crushing strength test. The test method was the same as that of Example 1. In the hard particle crack resistance test, the number of cracks generated in valve seat No. 1B was set as the reference (=1.0) to calculate the ratio of the number of cracks generated in the hard particles of the valve seat to the reference (crack generation ratio). In the wear test, the wear ratio of the valve seat was calculated by setting valve seat No. 1B as the reference (=1.00).
[0085] The valve seat No. 1B (conventional example) used as the reference in the hard particle crack resistance test and the wear test is a material used for valve seats on the intake side of general gasoline engines, and the functional member side layer is an iron-based sintered alloy material containing Co. The valve seat used on the intake side is required to have lower wear resistance than the valve seat used on the exhaust side.
[0086] The results are shown in Tables 15 and 16.
[0087] [Table 11]
[0088] [Table 12]
[0089] [Table 13]
[0090] [Table 14]
[0091] [Table 15]
[0092] [Table 16]
[0093] In the present invention (reference example), even though the matrix structure is composed of a high alloy phase and pearlite, the valve seat has the same or better wear resistance and sufficient radial crushing strength as the sintered body (conventional example No. 1B) with a composition containing Co, which has the same hardness level. For example, it can be said that the valve seat is fully applicable to intake side valve seats, which have a relatively low wear resistance requirement. [Explanation of symbols]
[0094] 1 Valve seat 2 Cylinder block equivalent material 3 Heating means 4 Valve
Claims
1. A valve seat press-fitted into a cylinder head of an internal combustion engine, the valve seat having a single-layer structure made of a functional component-side layer, The functional component side layer has a structure in which a matrix phase, 10 to 40% by area of hard particles, and 0 to 5% by area of solid lubricant particles are dispersed in the matrix phase, and the hard particles have a Vickers hardness of 700 to 1300 HV and a composition, by mass%, of 1.5 to 3.5% Si, 7.0 to 9.0% Cr, 35.0 to 45.0% Mo, 5.0 to 20.0% Ni, with the balance being Fe and unavoidable impurities. and the matrix portion including the matrix phase, the hard particles, and the solid lubricant particles contains, by mass%, C: 0.5 to 2.0%, Si: 0.2 to 2.0%, Mn: 5% or less, Cr: 0.5 to 15%, Mo: 3 to 20%, Ni: 1 to 10%, V: 0 to 5%, W: 0 to 10%, S: 0 to 2%, Cu: 0 to 5%, with the balance being Fe and unavoidable impurities. The density of the valve seat is 6.70 to 7.20 g / cm. 3 1. A valve seat made of an iron-based sintered alloy for an internal combustion engine, comprising:
2. 2. The iron-based sintered alloy valve seat for internal combustion engines according to claim 1, characterized in that the matrix phase of the functional component side layer has a structure consisting of 10 to 90% fine carbide precipitate phase, 0 to 30% high alloy phase, and the remainder pearlite, with the area ratio being 100% being the matrix phase area excluding the hard particles and the solid lubricant particles.
3. 2. The iron-based sintered alloy valve seat for internal combustion engines according to claim 1, characterized in that the matrix phase of the functional component side layer has a structure consisting of 0 to 15% of a high alloy phase and the remainder being a fine carbide precipitate phase, with the area ratio of the matrix phase excluding the hard particles and the solid lubricant particles being 100%.
4. 2. The iron-based sintered alloy valve seat for an internal combustion engine according to claim 1, characterized in that the matrix phase of the functional component side layer has a structure consisting of 0 to 25% of a high alloy phase and the remainder of a bainite phase, with an area ratio of the matrix phase excluding the hard particles and the solid lubricant particles being 100%.
5. 2. The iron-based sintered alloy valve seat for internal combustion engines according to claim 1, characterized in that the matrix phase of the functional component side layer has a structure consisting of 0 to 30% of a high alloy phase and the remainder being pearlite, with the area ratio of the matrix phase excluding the hard particles and the solid lubricant particles being 100%.
6. 4. The valve seat made of an iron-based sintered alloy for an internal combustion engine according to claim 2 or 3, characterized in that the fine carbide precipitate phase is a phase in which fine carbides having a grain size of 10 μm or less are precipitated and which has a Vickers hardness of 400 to 600 HV.
7. The solid lubricant particles are manganese sulfide (MnS), molybdenum disulfide (MoS 2 6. The valve seat made of an iron-based sintered alloy for an internal combustion engine according to claim 1, characterized in that the valve seat is made of one or two types selected from the following:
8. The valve seat made of an iron-based sintered alloy for an internal combustion engine as described in claim 6, characterized in that the solid lubricant particles are one or two types selected from the group consisting of manganese sulfide (MnS) and molybdenum disulfide (MoS 2 ).
Citation Information
Patent Citations
Abrasion resistant sintered member and manufacturing method therefor
JP2003119542A
Valve seat made of iron-based sintered alloy, and production method therefor
JP2004232088A
Hard-particle dispersion type iron-based sintered alloy
JP2005325436A
Iron-based sinter alloy valve sheet
JP2015178650A
Cu-BASED SINTERED ALLOY AND MANUFACTURING METHOD THEREFOR
JP2016060922A